Philosophical Foundations of Medical Law - De Campos, Thana; Herring, Jonathan; Phillips, Andelka M (Oxford University Press, 2019)
With advances in personalised medicine, the field of medical law is being challenged and transformed. The nature of the doctor-patient relationship is shifting as patients simultaneously become consumers. The regulation of emerging technologies is being thrown into question, and we face new challenges in the context of global pandemics. This volume identifies significant questions and issues underlying the philosophy of medical law. It brings together leading philosophers, legal theorists, and medical specialists to discuss these questions in two parts. The first part deals with key foundational theories, and the second addresses a variety of topical issues, including euthanasia, abortion, and medical privacy. The wide range of perspectives and topics on offer provide a vital introduction to the philosophical underpinnings of medical law.